Will Indigenous Ecological Knowledge Vanish? Assessing Persistence of the Celako kemali in Farming Practices among the Serawainese in Bengkulu, Indonesia - Suminar, Panji (Forest and Society, 2023)
Indonesia is home to many indigenous peoples who can preserve the environment through their traditions amid the increasing of external values ​​and lifestyles’ penetration. The following presents the indigenous ecological knowledge of the Serawai people in the form of the celako kemali. Based on insights from the Indigenous research methods, this study aims first to assess the persistence of the celako kemali as a method for farming practices. Second, to identify transmission patterns of the celako kemali among generations in the Serawai community. This study found that there were 19 types of celako kemali. The current analysis demonstrates that, out of the 19 celako kemali, three types have been completely abandoned, five are still in use but with minor modifications, and eleven are still valid by established standards. The first generation acquires knowledge from their parents through the internalization process within the family. This first generation still preserves and maintains the 19 celako kemali daily farming activities. The second generation acquires knowledge through internalization within the family and horizontally by sharing experiences with other farmers, but horizontal channels are more dominant. This generation knows the 19 types of the celako kemali, although they dare to modify five types without losing the essence of their body of knowledge. The third generation acquires knowledge through vertical and oblique transmission, in which the oblique channel is predominant. This third generation learns a lot from village elders unrelated to the family, teachers, and mass media. However, this generation has abandoned completely three types of the celako kemali.